Antibacterial and antifungal activities of Cymbopogon nardus essential oil - Mohamed Nor, Nurhanani; Abd. Samah, Othman (Penerbit USM, 2010)
Essential oils and their components are becoming increasingly popular as naturally occurring antimicrobial agents. In this study the chemical composition and antimicrobial activity of Cymbopogon nardus essential oils were determined. The essential oil components which were identified by GCMS analysis are as follows: β-terpinyl acetate, isopulegol, cis-geraniol, citronellyl formate, L-β-pinene, δ-cadinene, γ-elemene and seychellene. The minimum inhibitory concentration (MIC) of essential oils against a few selected pathogenic bacteria (Staphylococcus aureus ATCC 25923, Bacillus anthracis ATCC 14578, Pseudomonas aeruginosa ATCC 27853 and Escherichia coli ATCC 35218) and fungi (Candida albicans ATCC 10231 and Cryptococcus neoformans ATCC 90112) were determined using disc diffusion method. The essential oils showed slightly potent inhibitory effects with mean diameter of inhibition zones ranging from 7.5 mm to 9.0 mm. Similar results were also obtained for the fungi, where the essential oils showed inhibitory effects with slightly wider diameter of inhibition zones which ranged from 7.8 mm to 12.0 mm. All microorganisms showed sensitivity towards C. nardus except for P. aeruginosa. The MIC values against these microorganisms ranged from 4.69 mg/mL to 37.5 mg/mL. The findings thus indicate the possibility of exploiting C. nardus essential oil as an effective inhibitor for the growth of some pathogenic microorganisms in the field of medicine.